Spatial and temporal diffusion of house prices in the UK - Sean Holly; Mohammad Hashem Pesaran; Takashi Yamagata (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper provides a method for the analysis of the spatial and temporal diffusion of shocks in a dynamic system. We use changes in real house prices within the UK economy at the level of regions to illustrate its use. Adjustment to shocks involves both a region specific and a spatial effect. Shocks to a dominant region - London - are propagated contemporaneously and spatially to other regions. They in turn impact on other regions with a delay. We allow for lagged effects to echo back to the dominant region. London in turn is influenced by international developments through its link to New York and other financial centers. It is shown that New York house prices have a direct effect on London house prices. We analyse the effect of shocks using generalised spatio-temporal impulse responses. These highlight the diffusion of shocks both over time (as with the conventional impulse responses) and over space.
Keywords: C21; C23; 330; house prices; cross sectional dependence; spatial dependence